Respuesta :
Answer:
it's because we understand the concept easily
Step-by-step explanation:
4x-1= -2(x+1)
or, 4x-1= -2x+(-2)
or, 4x-1= -2x-2
or, 4x+2x= -2+1
or, 6x= -1
or, x= -1/6
Answer:-1/6
Step by step explanation:
4x - 1 = 2(x+1)
Move the terms
4x-1 = -2x -2
Collect the like terms
4x + 2x = -2+1
Calculate the terms
6x = -1
Divide both sides by 6
X= -1/6
Step by step explanation:
4x - 1 = 2(x+1)
Move the terms
4x-1 = -2x -2
Collect the like terms
4x + 2x = -2+1
Calculate the terms
6x = -1
Divide both sides by 6
X= -1/6